Kinetic study and removal of contaminants in the leachate treatment using subsurface wetlands at pilot scale (2017)
ABSTRACT: The treatment of stabilized leachate from the Curva de Rodas landfill site in Medellin, Colombia, was evaluated using horizontal subsurface flow constructed wetlands (HSSF) planted with Phragmites australis at pilot scale. Assays were performed in two stages: the first with hydraulic loads (q) of 0.015 and 0.030md-1 and the second with loads of 0.060 and 0.091md-1. A wetland without plants was used as a control. Removals of 71.9, 91.2 and 75.1% for COD, BOD5 and NH4 +-N, respectively, were obtained. Kinetic constants were determined for each q or hydraulic time retention for COD, BOD5 and NH4 +-N with ranges into 0.103 and 0.413d-1, 0.065 and 1.208d-1, and 0.113 and 0.418d-1; respectively, in accordance with a first order under piston flow. And by linear regressions had a magnitude of 0.246 d-1 for the removal of COD (R2 = 0.955), 0.299d-1 for NH4 +-N (R2 = 0.922) and 0.199d-1 for BOD5 (R2 = 0.140). The elimination of mercury, lead, arsenic and zinc was also evaluated, achieving removals of: 37.8-92.9% Hg, 29.9- 44.9%Pb, 7.9-77.6%As and 22.9-64.3%Zn, depending on the hydraulic load applied. The accumulation of these metals in the leaves, stems and roots (rhizomes) of Phragmites australis was found as: 0.575-3.201mgHgkg-1, 0.649-4.718mgPbkg-1, 3.548-39.376mgZnkg-1, and 19.4mgAskg-1